Podnikatelský záměr výroby kogeneračních jednotek - Gomola, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Cílem mé diplomové práce je zanalyzovat trh kogeneračních jednotek, vypracovat vnější a vnitřní analýzu vybrané firmy a znázornit výhodnost jednotlivých variant výroby a následného prodeje, či pronájmu daného produktu. Bude při tom nutné brát v úvahu všechny aspekty a podstupovaná rizika. Realizace tak rozsáhlého projektu je kapitálově náročná, proto vypracuji také finanční analýzu.

The goal of this Diploma thesis is to analyze market for cogeneration plants, make an external and internal analysis of specific company and illustrate the advantages for each production option and subsequent sale or lease of the product. It is also necessary to take in consideration all aspects and risks. The realization of such a vast project is difficult for capital, therefore financial analysis is also performed.
Business Plan of Cogeneration Units Production
Keywords: Kogenerační jednotka; projekt; podnikatelský záměr; konkurence; analýza.; Cogeneration plant; project; business plan; competition; analysis.